PERKEMBANGAN SANDI STRATIGRAFI INDONESIA: Sandi Stratigrafi Indonesia 1973-1996-2023 - Muljana, Budi (Bulletin of Scientific Contribution, 2024)
AbstrakRevisi Sandi Stratigrafi Indonesia berkorelasi dengan perkembangan data serta konsep keilmuan khususnya stratigrafi. Seiring juga dengan pola pemikiran dalam memahami serta memberlakukan data-data stratigrafi. Selama perkembangan Sandi Stratigrafi Indonesia 1973 kemudian 1996 dan yang terakhir 2023, telah mengalami banyak sekali perubahan paragdigma konsep stratigrafi. Mulai dari pendekatan deskriftif atau yang sering disebut dengan stratigrafi tradisional ke pendekatan deterministic atau sampai ke prediktif atau sering juga disebut dengan stratigrafi modern. Tulisan ini ingin memberikan informasi bahwa perkembangan Sandi Stratigrafi Indonesia hamper 50 tahun ini. Tujuannya adalah untuk mengakomodir perkembangan data, metode dan konsep stratigrafi.Kata kunci : Sandi Stratigrafi Indonesia, Stratigrafi tradisonal, Stratigrafi modern AbstractStratigraphic Indonesian Codes revision correlate with the development of data and knowledge concept, especially in stratigraphy.  It is related to the point of view within to understand and interpret for all stratigraphic data. During the development of Stratigraphic Indonesian Code starting from 1973, 1996 and the last 2023, has changed the outlook paradigm of stratigraphic concepts. Starting on descriptive approaching point view or it’s called a traditional stratigraphy to deterministic or predictive interpretations or called as a modern stratigraphy.  This paper tries to give brief information about the developments of Stratigraphic Indonesian Codes almost during 50th years. The main point is to be able accommodate the data, methods, and stratigraphic concept development.Keywords: Stratigraphic Indonesian Codes, traditional stratigraphy, modern stratigraphy